(untitled) (Rudarsko-geološko-naftni zbornik, 2022)
This paper presents the implementation of site-specific analysis in observing the performance of monumental building in Bengkulu City, Indonesia that is called the Lighthouse View Tower. This building was inaugurated in 2012. So far, the issue related to the performance of building after 10 years is still necessary to be presented. The objective of this study is to observe how is the performance of the building once the strong earthquake occurred. This study is first conducted by performing a site investigation. The information related to soil profile; ground motion of maximum earthquake occurred in Bengkulu City is collected. Furthermore, the site-specific response analysis is conducted to the site where the building stands. The result from site-specific response analysis, i.e., the actual spectral acceleration is obtained. The spectral acceleration is then used as the input parameter for finite element analysis to observe the performance of the building. The main goal of this study is to observe the structure health condition. The result shows that during the strong earthquake, the structure of the view tower is still reliable and in a good condition. The concern on the building maintenance should be emphasized. In general, the method implemented in this study could be used as the method to assess performance of structure in other areas.